Project management as a development tool for greening of enterprises of the national economy. Issue 1 (November 2021) - Shmatko, N; Bondar, Iu; Tokareva, V; Kovalenko, N; Klenin, O; Kotlubai, V
Abstract: The article reveals the essence of project management, the feature of which is the implementation of multifaceted technological characteristics and subject area of design solutions. It is proved that the methods of project management allow to analyze the issues and determine the objectives of the project, justify the project and develop an appropriate set of documents; determine the necessary amounts and sources of funding; identify the structure of the project and schedule its implementation; calculate the necessary resources, estimates and project budget. The peculiarities of project management as a tool for greening the development of enterprises of the national economy in the conditions of constant complication of doing business and finding ways to improve it in the context of improving the efficiency of economic activity are studied. The project activity is covered, covering all spheres of enterprise functioning, such as production, marketing and innovation activity, social sphere. It is substantiated that the wide application of the project approach to economic development has led to the efficiency and versatility of project tools that allow the company to adapt to the business environment, reduce uncertainty and ensure sustainable development in modern business conditions.